Modulation of Proteasomal Activity Required for the Generation of a Cytotoxic T Lymphocyte–defined Peptide Derived from the Tumor Antigen MAGE-3 - Valmori, Danila (The Rockefeller University Press, 1999)
We have analyzed the presentation of human histocompatability leukocyte antigen-A*0201–associated tumor peptide antigen MAGE-3(271–279) by melanoma cells. We show that specific cytotoxic T lymphocyte (CTL)-recognizing cells transfected with a minigene encoding the preprocessed fragment MAGE-3(271–279) failed to recognize cells expressing the full length MAGE-3 protein. Digestion of synthetic peptides extended at the NH(2) or COOH terminus of MAGE-3(271–279) with purified human proteasome revealed that the generation of the COOH terminus of the antigenic peptide was impaired. Surprisingly, addition of lactacystin to purified proteasome, though partially inhibitory, resulted in the generation of the antigenic peptide. Furthermore, treatment of melanoma cells expressing the MAGE-3 protein with lactacystin resulted in efficient lysis by MAGE-3(271–279)–specific CTL. We therefore postulate that the generation of antigenic peptides by the proteasome in cells can be modulated by the selective inhibition of certain of its enzymatic activities.